1995
DOI: 10.1111/j.1600-0773.1995.tb00113.x
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Auditory System, the Visual System, and Peripheral Nerve and Long‐Term Combined Exposure to Toluene and Ethanol in Rats

Abstract: Male pigmented rats (n = 36) were exposed to toluene and/or ethanol (1000 p.p.m. toluene in the inhaled air 21 hr/day, and 5.7-8.0% ethanol in the drinking water continuously) during 8 weeks. Electrophysiological recordings were made 1 week after the exposure. Auditory sensitivity (auditory brainstem response) was reduced only after exposures including toluene. At 20 kHz, ethanol antagonized toluene-induced loss of auditory sensitivity (P < 0.05). Flash evoked potentials were not affected in any group. In peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
1
4
0
1
Order By: Relevance
“…RARs have been shown to be activated by both ether and alcohol (1). Also, alcohol has been shown to increase the amplitude of the action potentials (15). In the present study, Diazinon PLUS reduced the frequency and amplitude of the action potentials.…”
Section: Pesticide and Lung Afferent Activitysupporting
confidence: 57%
“…RARs have been shown to be activated by both ether and alcohol (1). Also, alcohol has been shown to increase the amplitude of the action potentials (15). In the present study, Diazinon PLUS reduced the frequency and amplitude of the action potentials.…”
Section: Pesticide and Lung Afferent Activitysupporting
confidence: 57%
“…Several studies [20,28,29] have demonstrated that long-term exposure to ethanol alone had no effect on auditory sensitivity and did not cause any toxicity to the outer hair cells in rats. However, Morizono and Sikora [19] found a reduction in cochlear microphonics after topical application of alcohol to the inner ear of guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments which evaluated the effects of combined exposures to toluene and ethanol (2 of the solvents used in the studied company), revealed that exclusive exposure to ethanol did not affect the auditory system (32,33). In combination with toluene, ethanol exposure has been reported to impair rats' performance further in conditioned avoidance responses (32) and reduce (33) the effect of toluene on auditory sensitivity.…”
Section: Acoustic Reflex Measurementsmentioning
confidence: 99%